Perlindungan Hukum terhadap Konsumen Atas Penggunaan Suku Bunga Anuitas dalam Perjanjian Kredit Perbankan - Melisa Lani Safitri (Pusat Riset dan Inovasi Nasional, 2026)
Along with the increase in long-term credit products, banks began to switch to using the annuity interest calculation system. This shift in the interest rate calculation method causes losses for debtors who decide to make early repayments. This study aims to analyze the legal protection for debtors and the role of the OJK in protecting debtors regarding the use of annuity interest rates in banking credit agreements. The research method used in this study is normative legal research with a legislative approach, conceptual approach, and case approach. The legal materials in this study are primary, secondary, and tertiary legal materials. The processing of legal materials was carried out by collecting relevant legal materials and then analyzing them to answer the problems in the study. The results of the study show that the use of annuity interest rates causes debtors, who are essentially in a weak position, to suffer losses. The enactment of the UUPK and POJK is a form of legal protection provided by the state. Although the legal structure and substance are adequate, law enforcement by the OJK has not been effective due to legal culture factors. Banks are profit-oriented, while debtors have a passive legal culture. Based on the results of the study, it was concluded that the use of annuity interest rates indicates unfairness in the agreement, so debtors need to be protected. However, law enforcement by the OJK has not been effective due to obstacles in the legal culture of the parties.